2003
DOI: 10.1152/ajpendo.00502.2002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of α2-adrenergic receptors blunts epinephrine-induced lipolysis in subcutaneous adipose tissue during a hyperinsulinemic euglycemic clamp in men

Abstract: . Activation of ␣2-adrenergic receptors blunts epinephrine-induced lipolysis in subcutaneous adipose tissue during a hyperinsulinemic euglycemic clamp in men. Am J Physiol Endocrinol Metab 285: E599-E607, 2003; 10.1152/ajpendo.00502.2002The aim of this study was to investigate whether hyperinsulinemia modifies adrenergic control of lipolysis, with particular attention paid to the involvement of antilipolytic ␣2-adrenergic receptors (AR). Eight healthy male subjects (age: 23.9 Ϯ 0.9 yr; body mass index: 23.8 Ϯ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 25 publications
2
58
2
Order By: Relevance
“…Instead, inhibition of ␣-AR signaling may underlie the lipolytic effect of CST given its ability to prevent phenylephrine from activating PLC. Existing literature indicates that ␣-AR signaling inhibits lipolysis, whereas ␣-AR blockade potentiates the lipolytic effect of ␤-AR signaling (29,30,63,64). Acting like an ␣-AR antagonist, CST enhanced the lipolytic effect of ␤-AR agonists (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Instead, inhibition of ␣-AR signaling may underlie the lipolytic effect of CST given its ability to prevent phenylephrine from activating PLC. Existing literature indicates that ␣-AR signaling inhibits lipolysis, whereas ␣-AR blockade potentiates the lipolytic effect of ␤-AR signaling (29,30,63,64). Acting like an ␣-AR antagonist, CST enhanced the lipolytic effect of ␤-AR agonists (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The 50 % suppression of NEFA (palmitate) release is achieved with a concentration of free insulin of about 12 pmol/l (Jensen et al 1989). In addition, hyperinsulinaemia induces a reduction in the lipolysis-stimulating action of catecholamines (Stich et al 2003). Furthermore, insulin stimulates re-esterification of NEFA released from the adipocyte (stimulating the uptake of glucose and formation of glycerol-6-phosphate).…”
Section: Postprandial Statementioning
confidence: 99%
“…We also demonstrated that insulin was unable to modulate the lipolytic effect of ANP, even after relatively long-term treatment. Hyperinsulinemia impairs ␤-AR-dependent lipid-mobilizing effects in humans (Stich et al, 2003). Resistance to the antilipolytic action of insulin is an important characteristic of the ANP pathway that could have major pathophysiological importance.…”
mentioning
confidence: 99%